Metodologias de serviços públicos de ATER: estudo em instituições do Rio Grande do Norte - Cunha, Abdon Silva Ribeiro da (2012)
Due to the appreciation of family farming by the Brazilian Federal Government, the Technical Assistance and Rural Extension was induced to restructure and act in a more participative way, culminating in the National Policy of Technical Assistance and Rural Extension (PNATER), changing the profile of technology transfer and knowledge (diffusionism) for an action that uses participatory methodologies focused on exchange of knowledge between farmers and technicians. The process of discussion of the trends of ATER brought the New ATER , with the recognition of agroecology as the main guidance. This research aimed to analyze methods of public ATER developed by institutions of Rio Grande do Norte, under the guidance of New ATER. The research is qualitative. Secondary data were collected through documental research and literature. Primary data were collected through a set of interviews applied to representatives of public institutions ATER, namely EMATER-RN, Diaconia and AACC and representatives of organizations that receive public ATER. The research showed the difficulties of EMATER-RN in implementing of New ATER due to lack of infrastructure and low adherence of the new form of technical assistance and rural extension. It was shown also that the AACC and Diaconia act with ATER through projects with implementation deadlines set, often interrupting ATER while communities are still in need of assistance